1997
DOI: 10.1007/bf02267718
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of cardiac baroreceptor activity assessed non-invasively by spectral and sequence techniques

Abstract: Baroreceptor sensitivity (BRS) is increasingly used as a prognostic indicator in cardiovascular disease. Traditionally it has been measured using invasive techniques with pharmacological manipulation of blood pressure (BP). With the advent of newer methods to measure pulse interval and beat-to-beat changes in BP it is now possible, using sophisticated mathematical modelling techniques, to calculate cardiac BRS non-invasively. However, there are virtually no data on the reproducibility of these newer techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…This method was used widely in many studies to assess the BRS. [32][33][34] Both sequence methods and CSP further showed that BRS was decreased in patients with mild-tomoderate hypertension. 35 In our study, BRS in sequential analysis was found, as in the literature, 36,37 to depend on age, gender, DBP, SBP and HR.…”
Section: Discussionmentioning
confidence: 97%
“…This method was used widely in many studies to assess the BRS. [32][33][34] Both sequence methods and CSP further showed that BRS was decreased in patients with mild-tomoderate hypertension. 35 In our study, BRS in sequential analysis was found, as in the literature, 36,37 to depend on age, gender, DBP, SBP and HR.…”
Section: Discussionmentioning
confidence: 97%
“…The more frequently used method to obtain non-invasive estimates of cardiac BRS, frequency-domain analysis with the FFT algorithm, has intrinsic limitations regarding the temporal resolution that is required for continuous monitoring of BRS [12-14, 17, 19-22]. As an alternative, we explored a time-domain approach, derived from sequence analysis, a technique that is closer to the classical evaluation of BRS function based on drug-induced changes in BP [6,14,19]. In a previous investigation we studied the influence of the number of beats and the time lag of a moving window on the correlation (or the so-called cross-correlation) between Values are given as mean ± SD Table 2 Systolic blood pressure (SBP) and pulse interval (PI) values after tilt SBP and PI [16].We concluded that the ideal approach to improve the temporal resolution of sequence analysis is to use a moving window with only 3-beats and a time lag of 0 beats between the ABP and PI sequences [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that supine BRS measurements are reproducible in healthy elderly and hypertensive subjects using spectral and sequence analyses [14,15]. We wished to assess the changes in BRS before, during and after tilt and the changes that may recur to these measurements over a period of time using a novel mathematical model.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were examined using a standardized protocol [15]. They were asked to attend in the morning after abstinence from caffeine, nicotine or alcohol-containing products for at least 12 h and at least 2 h after breakfast.…”
Section: Methodsmentioning
confidence: 99%